Bibliometric Analysis of Publication Trends Related to Hizb Ut-Tahrir Indonesia (HTI) Before and After Dissolution - Andi Muhammad Farid Ramadhan; Surwandono Surwandono (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
The main objective of this study is to map the academic development and thematic shifts in research on Hizb ut-Tahrir Indonesia (HTI) before and after its official dissolution (2010-2023). Previous studies highlight HTI’s evolution as a transnational Islamic movement and the growing scholarly attention following the Indonesian government’s 2017 ban. Despite its termination, HTI remains central in academic debates on Islamic ideology and socio-political dynamics. This study employs a quantitative bibliometric method using Dimensions data to examine structural patterns in HTI research. VOSviewer is used to visualize co-authorship networks, keyword clusters, and institutional contributions. The findings reveal 402 publications, with a significant rise in output after HTI’s dissolution. Ideological contestation, da'wah strategies, and political activism dominate the thematic landscape. Indonesia remains the primary hub of HTI-related scholarship, with significant contributions from the University of Muhammadiyah Yogyakarta and PTIQ Institute Jakarta. Key thematic clusters include Islamic movements, political Islam, the caliphate discourse, constitutional debates, and liberal Islamic networks. These findings demonstrate HTI’s continuing relevance in discussions on Islamic identity and social movements in Indonesia. This study maps HTI’s scholarly trajectory and recommends expanding comparative analyses of post-ban transformations of transnational Islamic movements.Adam, Y. F. (2022). Islam dan Politik Identitas: Konflik pada Gerakan 212 dalam Perspektif Sejarah Indonesia. NALAR: Jurnal Peradaban Dan Pemikiran Islam, 6(2), 88-102. https://doi.org/10.23971/njppi.v6i2.4395Al-Amin, A. R. (2014). Demokrasi Perspektif Hizbut Tahrir Versus Religious Mardomsalari ala Muslimin Iran. ISLAMICA Jurnal Studi Keislaman, 8(September), 28-58. https://doi.org/10.15642/islamica.2013.8.1.28-58Al-hamdi, R. (2013). Islam and Politics : Political Attitudes of The Elites in Muhammadiyah 1998-2010. Indonesian Journal of Islam and Muslim Societies, 3(2), 267-290. Alvian, R. A. (2023). How Extremist Movements Delegitimise Religious Moderation Campaigns: A Case of Hizbut Tahrir Indonesia (2018-2022). Perspectives on Terrorism, 17(3), 23-41. https://doi.org/10.19165/MDOT2199Aswar, H. (2022a). Alternative Solution for Indonesian Political and Ideological Problems A Framing Analysis on Hizb ut-Tahrir Ideological Narratives. Intellectual Discourse, 30(1). https://doi.org/10.31436/id.v30i1.1846Aswar, H. (2022b). Nationalism Narrative and the State Policy on Hizbut-Tahrir in Indonesia. Nation State: Journal of International Studies, 5(2), 107-118. https://doi.org/10.24076/nsjis.v5i2.836Aswar, H., Yusof, D. B. M., & Hamid, R. B. A. (2020). Conflict Between Hizb Ut-Tahrir And Islamic Civil Society In Indonesia : A Countermovement Approach. Jurnal Al-Adalah : Jurnal Hukum Dan Politik Islam, 5(2), 183-203. https://doi.org/10.35673/ajmpi.v5i2.892Azizah, N., Muluk, H., & Milla, M. N. (2023). Pursuing Ideological Passion in Islamic Radical Group ’s Insurgency : a case study of Negara Islam Indonesia. Indonesian Journal of Islam and Muslim Societies, 13(1), 1-27. https://doi.org/10.18326/ijims.v13i1.1-27Azman, A. (2018). Gerakan dan Pemikiran Hizbut Tahrir Indonesia. Al Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 7(1), 99-113. https://doi.org/10.24252/ad.v7i1.5329Basyir, K. (2014). Gerakan Fundamentalisme Islam di Indonesia. Al-Tahrir, 14(Mei), 23-45.Dulkiah, M., Setia, P., & Rosele, M. I. (2023). Religious Movements and the Adoption of New Media: The Internet Used by Hizbut Tahrir Indonesia After Disbanded. Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 7(1), 11-26. awati, F., Minangsih, K., & Noorhayati, S. M. (2020). Observing HTI’s Da’wah Movement Following Perppu Number 2 of 2017 Concerning Community Organizations. ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 20(1 SE-Articles), 119-129. https://doi.org/10.14421/esensia.v20i1.1839Habibi, M., & Yahya, S. A. Bin. (2023). Politics and Processing in The Struggle of Hizbut Tahrir in Malaysia Politics and Processing in The Struggle of Hizbut Tahrir in Malaysia. International Journal of Academic Research in Business and Social Sciences, 1(6), 1827-1835. https://doi.org/10.6007/IJARBSS/v13-i6/16577Hayati, N. (2017). Konsep Khilafah IslᾹmiyyah Hizbut Tahrir Indonesia: Kajian Living al-Qur’an Perspektif Komunikasi. Epistemé: Jurnal Pengembangan Ilmu Keislaman, 12(1), 169-200. https://doi.org/10.21274/epis.2017.12.1.169-200Hermawan, S. (2021). Negara , Politik Identitas , dan Makar : Pandangan Organisasi Massa Islam Tentang Makar dan Upaya Pencegahannya Melalui PERPPU Ormas. Al-Ahkam: Jurnal Ilmu Syari’ah Dan Hukum, 6(2), 15-33. https://doi.org/https://doi.org/10.22515/alahkam.v6i1.3993Hew, W. W. (2018). The Art of Dakwah: social media, visual persuasion and the Islamist propagation of Felix Siauw. Indonesia and the Malay World, 46(134), 61-79. https://doi.org/10.1080/13639811.2018.1416757Hilmy, M. (2013). The Politics of Retaliation : The Backlash of Radical Islamists to Deradicalization Project in Indonesia. Al-Jami’ah, 51(1), 130-158.Hook, D. W., Porter, S. J., & Herzog, C. (2018). Dimensions : Building Context for Search and Evaluation. Frontiers in Research Metrics and Analytics, 3(August), 1-11. https://doi.org/10.3389/frma.2018.00023Huda, A. (2010). Epistemologi Gerakan Liberalis , Fundamentalis , dan Moderat Islam di Era Modern. De Jure: Jurnal Hukum Dan Syar’iah, 2(2), 187-188. https://doi.org/10.18860/j-fsh.v2i2.2977Ichwan, M. N. (2011). Official Ulema and The Politics of Re-Islamization : The Majelis Permusyawaratan Ulama , Authority In Post-New Order Aceh. Journal of Islamic Studies 22:2, 2(April), 183-214. https://doi.org/10.1093/jis/etr026Iqbal, A. M. (2014). The revolution of information and communication technology has transformed the world into different shape , including Muslim world . This technology in the form of. Islamika Indonesiana, 1(1), 81-105. https://doi.org/https://doi.org/10.15575/isin.v1i1.42Irkhami, N. (2014). The Economic-Political Concept of Hizbut Tahrir Indonesia: Reflection on The Early Islamic Thoughts. Indonesian Journal of Islam and Muslim Societies, 4(1), 105-134. https://doi.org/10.18326/ijims.v4i1.105-134Juliansyah, V. (2017). Penyebaran Paham Radikal dan Ide Bentuk Negara Kekhalifahan di Tengah Masyarakat Kota Pontianak. PROYEKSI Jurnal Ilmu-Ilmu Sosial Dan Humaniora PROYEKSI Jurnal Ilmu-Ilmu Sosial Dan Humaniora (e-Journal), 22(2). https://doi.org/10.26418/proyeksi.v22i2.2440Junaedi, D. (2012). Bendera di Hizbut Tahrir Indonesia Daerah Istimewa Yogyakarta. Kawistara, 2(3), 264-275.Kibtiah, T. M., & Putri, M. R. (2021). The Existence of Hizbut Tahrir Indonesia: Strategies for Engaging in Indonesian Politics. Indonesian Journal of Political Research (IJPR), 2(December), 93-108.Kusuma, M. H. (2019). Pembubaran Hizbut Tahrir Indonesia oleh Pemerintah Republik Indonesia dalam Pandangan Hukum Islam dan Konstitusi Indonesia. Fakultas Syariah Universitas Islam Negeri Raden Intan Lampung, 1(1), 135.Maksum, A. (2017). Discourses on Islam and Democracy in Indonesia: A Study on the Intellectual Debate between Liberal Islam Network (JIL) and Hizbut Tahrir Indonesia (HTI). Journal of Indonesian Islam, 11(02), 405-422. https://doi.org/10.15642/JIIS.2017.11.2.405-422Marfiando, B. (2020). Pembubaran Hizbut Tahrir Indonesia ( HTI ) Ditinjau dari Kebebasan Berserikat. Jurnal Ilmu Kepolisian, 14(2), 89-101. https://doi.org/10.35879/jik.v14i2.253Muazaroh, S. (2019). Pembubaran Hizbut Tahrir Indonesia Perspektif Maqashid: Otoritas atau Otoritarianisme. Justicia Islamica: Jurnal Kajian Hukum Dan Sosial, 16(1), 103-120. https://doi.org/10.21154/justicia.v16i1.1622 Muhammad, F. (2017). Studi Fenomenologi Tentang Makna Ideologi Khilafah dan Politik Aktivis Izbut Tahrir di Pekanbaru. Fenomenologi, 8(1), 1-16.Muharam, M. M., Marijan, K., & Kusman, A. P. (2021). Power Relation of the 212 Islamic Group and The Government in the 2019 Presidential Election. Masyarakat, Kebudayaan dan Politik, 34(3), 305-316.Muhsin, I. (2012). Gerakan Penegakan Syariah : Studi Gerakan Sosial Hizbut Tahrir Indonesia di DIY. Ijtihad, Jurnal Wacana Hukum Islam Dan Kemanusiaan, 12(1), 43-61.Muhsin, I., Rochmawati, N., & Huda, M. C. (2019). Revolution of Islamic Proselytizing Organization: From Islamism to Moderate. Qudus International Journal of Islamic Studies, 7(1), 45-70. https://doi.org/10.21043/qijis.v7i1.5076Munabari, F. (2018). The Quest for Sharia in Indonesia: The Mobilization Strategy of the Forum of Islamic Society. Contemporary Islam, 12(3), 229-249. https://doi.org/10.1007/s11562-018-0416-zNurhakim, M. (2011). Gerakan Revivalisme Islam dan Wacana Penerapan Syariah di Indonesia : Telaah Pengalaman PKS dan Salafi. Ulul Albab, 12(1), 1-14.Osman, M. N. M. (2010). Reviving the Caliphate in the Nusantara: Hizbut Tahrir Indonesia’s Mobilization Strategy and its Impact in Indonesia. Terrorism and Political Violence, 22(4), 601-622. https://doi.org/10.1080/09546553.2010.496317Perez, J. G. (2011). Islamización En Indonesia : Acción Política Del Partido De La Justicia Y La Prosperidad. Estudios de Asia y África Xlvi:, 3, 525-558.Qodir, Z., & Latief, S. (2011). Kelangsungan dan Perlawanan Politik Identitas dalam Bingkai Keadaban Demokrasi. Jurnal Studi Pemerintahan, 2(1), 193-224. http://dx.doi.org/10.18196/jgp.2011.0010Rahman, M. T., Bukhori, & Setia, P. (2023). Hizbiyyah and Hizbut Tahrir Indonesia ’ s New Member Recruitment Strategy After Disbandment. FIkrah: Jurnal Ilmu Aqidah Dan Studi Keagamaan, 11(1), 41-64. https://doi.org/10.21043/fikrah.v8i1.Rasyad, I., & Yumitro, G. (2023). Bibliometric analysis on the international publication of muslim brotherhood. Communications in Humanities and Social Sciences, 3(1), 1-8. https://doi.org/10.21924/chss.3.1.2023.54Rijal, S. (2022). The Origins of Hizbut Tahrir Indonesia : Global And Local Interactions. Islamic Studies Review, 1(1), 110-127.Rokhmad, A. (2012). Radikalisme Islam dan Upaya Deradikalisasi Paham Radikal Abu Rokhmad. Walisongo, 20(1), 79-114.Rubino, R., Hatta, M., & Abdullah. (2017). Communication Technique of Hizbut Tahrir Indonesia (HTI) in The Development of Cadre in North Sumatera. IJLRES: International Journal on Language, Research (LAW) Education Studies, 1(2), 240-255. http://dx.doi.org/10.47006/ijlres.v1i2.1023Sahid, H. M. (2014). Contesting Caliphate: Opposition of Indonesian fundamentalist groups to ISIS caliphate. Journal of Indonesian Islam, 8(2), 185-208. https://doi.org/10.15642/JIIS.2014.8.2.185-208Setiawan, T. (2025). The Caliphate as the Global Islamic Politics: Theological, Historical, and Contemporary Discourse Perspectives. Jurnal Review Politik, 15(1 SE-Articles), 64-84. https://doi.org/10.15642/jrp.2025.15.1.64-84Shofwan, A. M. (2016). Pandangan Hizbut Tahrir Terhadap Radikalisme Gerakan Isis Dalam Menegakkan Daulah Khilafah. ADDIN, 10(1), 141-162.Sihidi, I. T., Roziqin, A., & Suhermanto, D. F. (2020). Pertarungan Populisme Islam dalam Pemilihan Presiden 2019. JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 5(2), 174-189. https://doi.org/DOI: 10.14710/jiip.v5i2.8516Sudarman. (2017). Khilafah Dalam Pemikiran Hizbut Tahrir Indonesia. KALAM, 11(1), 107-134.Wahid, A., Saputra, Y., & Ali, W. Z. K. W. (2024). Perjuangan HTI dalam Sistem Kenegaraan di Indonesia dan Metamorfosisnya di Media Online. Temali: Jurnal Pembangunan Sosial, 7(1), 47-56. https://doi.org/https://doi.org/10.15575/jt.v7i1.30064Zulkarnain, F. (2020). The Political Thought and Movement of Hizbut Tahrir Indonesia (HTI). Journal of Critical Reviews, 7(1), 478-482. https://doi.org/https://doi.org/10.31838/jcr.07.01.94